High Spatial Variability of Biomass Burning Emissions Observed at Three Tibetan Plateau Sites. Issue 11 (11th November 2022) - Zhu, Chong‐Shu; Qu, Yao; Zhang, Zhi‐Sheng; Zhang, Ting; Dai, Wen‐Ting; Cao, Jun‐Ji
Abstract: Aerosol from biomass burning (BB) can affect regional and global climate by changing radiation balance and cloud properties, especially over the high altitude environ‐vulnerable region. To investigate the contributions of BB on atmospheric particulate matter trans‐the Tibetan Plateau (TP), the total suspended particle samples were collected at three high altitude sites over the northeastern (Qinghai lake, 3, 200 m a.s.l.), central (Beiluhe, 4, 659 m a.s.l.), and southwestern TP (Ngari, 4, 360 m a.s.l.), respectively. Highly spatial variations of BB tracers (including levoglucosan, mannosan, and galactosan) were obtained. Elevated BB tracer concentrations were observed in the northeastern and southwestern sites compared to the central TP site. The heighten concentrations of particulate matter from biomass burning and organic carbon from biomass burning were obtained at Ngari (with 5260.3 and 2257.7 ng m −3 ) and Qinghai lake (with 1508.8 and 647.6 ng m −3 ) compared with those at Beiluhe (with 18.8 and 8.1 ng m −3 ), respectively. The results indicated that the BB contributions to aerosol were significant on the margin of the TP. In addition to the long‐range transport of BB pollutant, the local emissions may be an important contributor in the northeastern and southwestern TP. The present study can improve the understanding of BB characteristics and effects in the TP. Plain Language Summary: The Tibetan Plateau (TP), known as the "Third Pole, " is a vulnerable region for the climate and global environmental change. Biomass burning (BB) from the surrounding area and local emissions can contribute to the aerosol mass, and influence the environment and climate change. Elevated BB tracers concentrations were observed in the northeastern and southwestern sites compared to the central TP site. The results indicated that the BB contributions to aerosol were significant on the edge of the TP. In addition to the long‐range transport of BB, the local emissions may be an important contributor in the northeastern and southwestern TP. Key Points: The spatial variability of biomass burning (BB) tracer was obtained trans‐the "Third Pole" firstly The BB contributions to aerosol were significant in the southwestern Tibetan Plateau The major potential source distributions of BB were identified